2011
DOI: 10.1109/mprv.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Paying Attention to the Man behind the Curtain

Abstract: Keywords: human supervisory control, decentralized systems, human-computer interface, smart grid, decision support, power plantsIn the push to develop smart energy systems, there is increasing focus on how to design systems that measure and predict user behavior in order to effect optimal energy consumption. While such focus is clearly an important component in the success of these future systems, substantially less attention is paid to the human on the other side of the energy system loop -the supervisors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…For analysing the human-automation interaction, several researchers have developed various frameworks [1][2][3]. In [40], we suggested a framework for shared-control continuous-time systems, such that through providing a low-level control input as well as a reference trajectory, the user-interacts with an automated system.…”
Section: Framework For Human-automation Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…For analysing the human-automation interaction, several researchers have developed various frameworks [1][2][3]. In [40], we suggested a framework for shared-control continuous-time systems, such that through providing a low-level control input as well as a reference trajectory, the user-interacts with an automated system.…”
Section: Framework For Human-automation Interactionmentioning
confidence: 99%
“…1 to meet the requirements of a task formulated in (3). Hence, we should evaluate whether the user has access to the required information to attain situation awareness regarding the task.…”
Section: Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unexpected increase in an operator's workload with increased automation is considered in [32] in the context of smart energy systems. How performance can be boosted by humans providing guidance to automated planners in path planning and resource allocation tasks is studied in [33].…”
Section: Human-in-the-loop Controlmentioning
confidence: 99%
“…Automated algorithms also have a variety limitations, particularly in terms of brittleness and the inability to easily recognize patterns within the environment 4 . Recent research 5 has shown that by allowing high-level interaction between human operators and automated planning systems, overall increases in system performance can be seen. The key in this phenomenon is the appropriate allocation of tasks between human and automation.…”
Section: Introductionmentioning
confidence: 99%